(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
The present investigation aims to examine the diabetic potential of the plant Ficus racemosa in normal and alloxan induced diabetic rats. The bark extract with water, petroleum ether and with alcohol were screened for blood glucose lowering activity and the alcoholic extract having better therapeutic potential was prepared through Soxhlet extraction for further study. Alcoholic and aqueous extract of bark of Ficus racemosa at a dose of 400 mg/Kg was given to normal and alloxan induced diabetic rats and the blood samples taken from the retero-orbital plexus vein were analyzed for blood glucose level as per standard protocol with available kits through Auto-analyzer. The comparison of blood sugar level as per model schedule showed that in normal group the ethanolic extract, at a dose of 400 mg/Kg intra-peritoneal, the blood glucose lowering 28.66 % while in aqueous extract given group it was 25.90 %. In alloxan induced diabetic rats decrease in blood glucose level in aqueous and ethanolic extract group was found to be 27.01 % and 45.03 % respectively. In conclusion, the ethanolic extract of Ficus racemosa reflected anti-diabetic potential through its glucose lowering activity in experimental animals. It supported the folklore claim of anti-diabetic activity of the plant.